The reinforcing effect of anti-caries treatments on acidic challenge resistance of irradiated enamel - Fereshteh Shafiei; Iman Khaleghi; Mansour Ansari; Esmaeil Mirzaei; Maryam S. Tavangar (PLoS ONE, 2026)
Aim To investigate the effect of applying the following anticaries treatments on the surface microhardness (SMH) of irradiated enamel after pH-cycling: Nanohydroxyapatite (nano-HA), resin infiltration (RI), combination of nano-HA and RI, or curcumin-loaded mesoporous nano-silica (Cur/MSN). Methodology In this in vitro experimental study, 30 sound molars were mesiodistally sectioned into two halves, yielding 60 enamel samples, and randomly divided into six groups (n = 10). Group 1 was kept as non-irradiated. The samples from the other five groups were subjected to fractionated X-ray radiation for 6 weeks, with a total dose of 60 Gy, delivered in 2 Gy fractions 5 days per week. After irradiation, each group was processed as follows: 2) no treatment; 3) treated with 15% nano-HA; 4) treated with RI; 5) treated with a combination of 15% nano-HA and RI; 6) treated with Cur/MSN (3 mg/ml). The initial SMH (SMH 0 ) was measured after irradiation and the final (SMH 1 ) after anticaries treatments and pH cycling. pH cycling consisted of a 3-hour immersion in a demineralizing solution, followed by 21 hours in a remineralization solution at 37 °C for 5 days. The surface micromorphology of irradiated groups after pH-cycling was assessed. Results Mean [±SD] SMH 0 of irradiated enamel was significantly lower than that of the non-irradiated one (330.7 ± 23.6 vs 262.9 ± 28.8; P < 0.001). Irradiated enamels treated with all anti-caries treatments showed a significantly higher SMH 1 compared to those of no-treatment (192.2 ± 28.7; all P < 0.01). SMH 1 of Ir/nano-HA (302.2 ± 16.4) or Ir/nano-HA + RI (305.4 ± 22.1) groups were higher than those of Ir/RI (245.5 ± 35.1; P < 0.001) and not different from Ir/Cur/MSN group (285.9 ± 16.4; P = 0.638 and 0.435 respectively). The increase in SMH 1 compared to SMH 0 (ΔSMH) was significant only in Ir/nano-HA (39.0; P = 0.003) and Ir/nano-HA + RI groups (42.9; P = 0.001). Conclusion Treatment with nano-HA and a combination of nano-HA with RI demonstrated significant potential to improve the resistance of the irradiated enamel surface to acidic challenges.